The impact of geriatric syndromes on quality of life among older people living with HIV in Kampala, Uganda - Senkoro, Elizabeth; Mbabazi, Phoebe; Banturaki, Grace; Naikoba, Suzan; Castelnuovo, Barbara (Frontiers in Public Health, 2024)
Older people living with HIV (OPWH) often have lower quality of life (QoL) compared to general population.Measuring their QoL is an important step in HIV care to ensure they have long healthy lives. This study aimed to evaluate the quality of life and its associated factors among people living with HIV aged 60 years and above in Uganda.We used a cross-sectional analysis of older people living with HIV (OPWH) enrolled in a prospective cohort from December 2020 -December 2021. Quality of life was assessed using the World Health Organisation QoL OLD instrument (WHOQOL-OLD). Linear regression model was used to determine associated factors.Of the 500 participants enrolled, 51.2% were men and their median age was 64 years (IQR: 62 -68).WHOQOL-OLD mean score(SD) was 90.1(8.3) out of 120. Factors that increased overall QoL were (Coefficient [95% Confidence Interval]): being male 2.35 (1.21 -3.73), having an income of ≥1 1.30 (-0.16 -2.76) and paradoxically having more than 2 non-communicable diseases 0.69 (-0.76 -2.14) in the past, present and future domain of QoL. Those that decreased QoL in the overall and various domains included: an increasing number of geriatric syndromes, depression, pre-frailty, frailty, malnutrition, and low physical function.Our findings suggest that financial stability contributed to good QoL while geriatric syndromes decreased QoL for OPWH. Integrating the screening and management of geriatric syndromes into HIV care has the potential to improve the overall QoL of OPWH.